Pitz status, recent measurements and tests - Krasilnikov,M.B. (2015)
The Photo Injector Test facility at DESY, Zeuthen site (PITZ) is dedicated to the development and optimization of a high-brightness electron source for the European XFEL. Recently a significant upgrade has been done at the facility. A new RF system has been installed for the PITZ gun, enabling higher attainable peak power in the cavity which is important for efficient LLRF regulation. First long-term tests for a stable gun operation at high duty cycle have been performed. Two major components for electron beam diagnostics - a transverse deflecting cavity for time resolved electron bunch characterization, and a second high energy dispersive arm for precise longitudinal phase space measurements - have been installed. First results of their commissioning will be reported. Copyright © 2012 by the respective authors.